2009
DOI: 10.1002/app.30165
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning fabrication and characterization of poly(vinyl alcohol)/montmorillonite nanofiber mats

Abstract: Poly(vinyl alcohol) (PVA)/montmorillonite clay (MMT) nanofiber mats have been fabricated by the electrospinning technique. The PVA/MMT nanofiber mats were characterized by X-ray diffraction (XRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Fourier transform infrared (FTIR), and mechanical measurements. The study showed that the introduction of MMT results in improvement in tensile strength, and thermal stability of the PVA matrix. XRD patterns and SEM micrographs suggest the coexiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 32 publications
(22 reference statements)
4
49
0
Order By: Relevance
“…Fibers were collected on an electrically grounded aluminum foil placed at 15 cm vertical distance to the needle tip (Tip-Collector Distance, TCD). The above spinning conditions were found being the best condition to make PVA based nanofibers in our previous report Karim et al, 2009;Lee et al, 2009a;Lee et al, 2009b;Park et al, 2009;Park et al, 2010). Figure 5 demonstrates FE-SEM and TEM images of PVA, PVA/MMT and PVA/MMT/Ag nanofibers electrospun with 5 wt.% of MMT and 5 wt.% of Ag nanoparticles.…”
Section: Methodsmentioning
confidence: 75%
“…Fibers were collected on an electrically grounded aluminum foil placed at 15 cm vertical distance to the needle tip (Tip-Collector Distance, TCD). The above spinning conditions were found being the best condition to make PVA based nanofibers in our previous report Karim et al, 2009;Lee et al, 2009a;Lee et al, 2009b;Park et al, 2009;Park et al, 2010). Figure 5 demonstrates FE-SEM and TEM images of PVA, PVA/MMT and PVA/MMT/Ag nanofibers electrospun with 5 wt.% of MMT and 5 wt.% of Ag nanoparticles.…”
Section: Methodsmentioning
confidence: 75%
“…2a, the electrospinning voltages significantly affected morphology of the CMs; at 10 kV, the microspheres were not fabricated while micron-sized spheres were obtained for 2.5 and 5.0 kV. Several studies previously indicated that fiber diameters could be controlled by changing electrospinning voltages (33)(34)(35). Electrospinning is sputtering and curling of charged jets upon voltage differences.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the increase in the CNC concentration in the fibres led to a significant enhancement of mechanical properties [9]. Electrospun PVA fibres have been extensively studied to understand the effects of molecular weight [10], concentration [9] and the presence of additives on mechanical properties and thermal stability [11]. Polystyrene (PS), another commodity polymer, has also been electrospun into fibres [12].…”
Section: Introductionmentioning
confidence: 99%